Literature Study on The Development of Artificial Intelligence in Education - Franky Gerald Cliford Manoppo; Shallom Aurelly Warouw; Claudio Reinaldo Woran; Jovan Putra Sihombing; Julianus Melale (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Background: This literature review aims to provide a comprehensive overview of the direction of AI development in education and offer strategic recommendations for sustainable, ethical, and responsible implementation. Objective: This study is a literature review aimed at examining and analyzing the development and application of artificial intelligence (AI) in the field of education. Methods: A quantitative approach was employed through a survey involving 450 respondents representing students, lecturers, and administrative staff at University X. The survey was complemented by a six-month content analysis of the institution’s official social media accounts (January–June 2024). Data were analyzed using descriptive statistics and simple regression. Results: However, despite the substantial opportunities offered, the implementation of AI also faces several challenges, including infrastructure limitations, ethical issues related to personal data usage, and the readiness of human resources within educational environments. Conclusion: Based on an extensive review of various scientific sources, the study finds that AI technology has been widely adopted across multiple educational aspects, including adaptive learning systems, intelligent tutoring systems, and learning analytics. AI has demonstrated a significant contribution to enhancing the effectiveness and efficiency of learning processes, strengthening personalized learning, and simplifying academic administrative management.